1981
DOI: 10.1093/ajcn/34.11.2367
|View full text |Cite
|
Sign up to set email alerts
|

Plasma zinc in hypertension/toxemia and other reproductive variables in adolescent pregnancy

Abstract: A study was conducted at Charity Hospital, New Orleans, among 272 adolescent pregnant women to ascertain the relationship of pregnancy outcome to plasma zinc level measured once at the time of enrollment. Regression analyses were performed on zinc status versus parameters concerning success of pregnancy corrected for gestational stage at specimen collection. Analysis of variance was performed on groups according to presence or absence of complications, with analyses of covariance used to analyze dichotomous gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…Dietary zinc deficiency has been postulated in young women who are not pregnant in West Scotland.22 The present study did not examine maternal intake but confirms the high plasma zinc concentrations reported in mothers of low birthweight infants during pregnancy.23 24 No overt pre-eclampsia occurred in our mothers of low birthweight infants. These same mothers had lower mean white blood cell zinc concentrations than mothers of normal birthweight infants at 28 weeks' gestation, at delivery, and at two months post partum.…”
Section: Discussionsupporting
confidence: 68%
“…Dietary zinc deficiency has been postulated in young women who are not pregnant in West Scotland.22 The present study did not examine maternal intake but confirms the high plasma zinc concentrations reported in mothers of low birthweight infants during pregnancy.23 24 No overt pre-eclampsia occurred in our mothers of low birthweight infants. These same mothers had lower mean white blood cell zinc concentrations than mothers of normal birthweight infants at 28 weeks' gestation, at delivery, and at two months post partum.…”
Section: Discussionsupporting
confidence: 68%
“…Twelve studies were identified that measured maternal circulating zinc in countries where inadequate zinc intake is predicted to be <17%, and looked at the association with birthweight (Table 1) [38,46,47,48,49,50,51,52,53,54,55,56]. Only one study, based on 3817 women in China, reported a 3.4-fold increase in the risk of delivering a LBW infant with serum zinc <560 µg/L (adjusted RR: 3.41, 95% CI: 1.97, 5.91) [56].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study, based on 3817 women in China, reported a 3.4-fold increase in the risk of delivering a LBW infant with serum zinc <560 µg/L (adjusted RR: 3.41, 95% CI: 1.97, 5.91) [56]. This is in contrary to two studies that reported significantly higher zinc concentrations in women with an SGA infant in the third trimester [47,55]. However, these findings were based on a relatively small number of women: 40–51 pregnant women including 10–16 women with SGA.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 Low serum Zn concentrations in preeclampsia mothers have been suggested to be partly due to reduced oestrogen and zinc binding-protein levels. 17 Placental Zn concentration has also been shown to be lower in preeclampsia in cross-sectional retrospective studies with placental Zn values positively correlating with birth weights.…”
Section: Discussionmentioning
confidence: 99%